Estimating the Import Content of Argentine Exports - Anos-Casero, Paloma; de Astarloa, Bernardo Diaz (2012)
Despite recent efforts toward collecting evidence of vertical specialization for developed economies, scarce work has been dedicated to developing economies and to Argentina, in particular. The key contribution of this paper is to provide comparable estimates of vertical specialization as reflected in the imported content of exports in Argentina. Drawing on the 1997 input-output matrix for Argentina, the authors estimate that the imported content of the country s exports is about 14.5 percent of total exports, lower than for other emerging economies. They also provide estimates of imported content for more disaggregated product categories.